Characteristics of Chinese herbal medicine usage and its effect on survival of lung cancer patients in Taiwan. (1st March 2018) - Li, Te-Mao; Yu, Yang-Hao; Tsai, Fuu-Jen; Cheng, Chi-Fung; Wu, Yang-Chang; Ho, Tsung-Jung; Liu, Xiang; Tsang, Hsinyi; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Li, Ju-Pi; et al.
Abstract: Ethnopharmacological relevance: In Taiwan, lung cancer remains one of the deadliest cancers. Survival of lung cancer patients remains low, ranging from 6% to 18%. Studies have shown that Chinese herbal medicine (CHM) can be used to induce cell apoptosis and exhibit anti-inflammatoryanti-inflammatory activities in cancer cells. Aim of the study: This study aimed to investigate the frequencies and patterns of CHM treatment for lung cancer patients and the effect of CHM on their survival probability in Taiwan. Materials and methods: We identified 6939 lung cancer patients (ICD-9-CM: 162). We allocated 264 CHM users and 528 CHM-non users, matched for age, gender, duration, and regular treatment. Chi-square test, conditional multivariable logistic regression, Kaplan-Meier method, and the log-rank test were used in this study. Results: The CHM group was characterized by a longer follow up time and more cases of hyperlipidemia and liver cirrhosis. This group exhibited a lower mortality hazard ratio (0.48, 95% confidence interval [0.39–0.61], p < 0.001), after adjusting for comorbidities. The trend was also observed that the cumulative survival probability was higher in CHM than in non-CHM users ( p < 0.0001, log rank test). Analysis of their CHM prescription pattern revealed that Bu-Zhong-Yi-Qi-Tang (BZYQT), Xiang-Sha-Liu-Jun-Zi-Tang (XSLJZT), and Bai-He-Gu-Jin-Tang (BHGJT); and Bei-Mu (BM), Xing-Ren (XR) and Ge-Gen (GG) were found to be the top three formulas and herbs, respectively. Among them, BM was the core CHM of the major cluster, and Jie-Geng (JG) and Mai-Men-Dong-Tang (MMDT) were important CHMs by CHM network analysis. Conclusion: The use of CHM as an adjunctive therapy may reduce the mortality hazard ratio of lung cancer patients. The investigation of their comprehensive CHM prescription patterns might be useful in future large-scale, randomized clinical investigations of agent effectiveness, safety, and potential interactions with conventional treatments for lung cancer patients. Graphical abstract: